Pneumatic Prehensile Gripper for Slender Objects with Embedded Fiber Reinforcement Structures - Zhonghua Guo; Mohammad Hossein Movahedi (Proceedings, 2024)
Tendril-like structures curl around plant stalks and can be regarded as effective manipulators of objects [...]